PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PENDIDIKAN AGAMA ISLAM BERBASIS ADOBE FLASH PROFESSIONAL CS6 UNTUK MENDUKUNG IMPLEMENTASI KURIKULUM 2013 - Nur Hamidi (Jurnal Pendidikan Agama Islam, 2017)
This study aims to produce a media interactive learning of Islamic education based on Adobe Flash Professional CS6 to support the implementation of the 2013 curriculum. The development model used is an ADDIE model. There are four stages of ADDIE development procedures, through which namely Analysis, Design, Develop, Implementation and Evaluation. This Media Interactive Learning of Islamic Education was based on Adobe Flash Professional CS6 which was evaluated by a media expert, a material expert, an IT expert, 2 peer reviewers and 2 PAI teachers. Limited trial was conducted on 10 students of class X SMP 1 Prambanan Yogyakarta to determine their responses to the product of media interactive learning of Islamic education based on Adobe Flash Professional CS6. Instrument used was a questionnaire check list. Results of limited testing of student responses indicated that media interactive learning of Islamic education based on Adobe Flash Professional CS6 had Good quality (79.71%). It canbe concluded that the media interactive learning based on Adobe Flash Professional CS6 fits as a source of learning Islamic education and it can be used in teaching Islamic education in relation to the implementation of the curriculum 2013.